Return from the choppy waters of the Indo-Pacific: Implications of the deployment of the Frigate Bayern - Alexandra Sakaki; Göran Swistek (Stiftung Wissenschaft und Politik (SWP), 2022)
After a voyage through the Indian and Pacific Oceans lasting almost seven months, the frigate Bayern has returned to Wilhelmshaven. Above all, Germany's intention in sending the ship was to signal its political willingness to be more actively involved in the stability and security of the Indo-Pacific. Retrospectively, the mission has helped to vitalize and deepen relationships with partners in the region through military and diplomatic dialogues as well as combined exercises by the armed forces. It is now crucial to maintain the relationship momentum this has created, for instance by continuing with consultations. However, Germany has not lived up to the claim - or just barely - that the frigate's voyage would contribute to maintaining the existing rules-based order and international law. It remains to be seen what conclusions Germany will draw for future engagement in the Indo-Pacific.
Keywords: 320